Memories of the Revolution : The First Ten Years of the WOW Café Theater - Dolan, Jill, 1957-; Tropicana, Carmelita; Hughes, Holly, 1955 March 10- (Triangulations., 2015)
The women's experimental theater space called the WOW Cafe (Women's One World) has been a vital part of New York's downtown theater scene since 1980. Since that time, WOW has provided a place for feminist and particularly lesbian theater artists to create, perform, and witness a cultural revolution. Its renowned alumnae include playwright and actor Lisa Kron, performance artists Holly Hughes and Carmelita Tropicana, the theater troupe the Five Lesbian Brothers, and actors/playwrights Peggy Shaw, Lois Weaver, and Deb Margolin, among others. Memories of the Revolution collects scripts, interviews, and commentary to trace the riotous first decade of WOW. While the histories of other experimental theater collectives have been well documented, WOW's history has only begun to be told. The anthology also includes photographs of and reminiscences by Cafe veterans, capturing the history and artistic flowering of the first ten years of this countercultural haven.